Initial Esophageal Anastomosis Diameter Predicts Treatment Outcomes in Esophageal Atresia Patients With a High Risk for Stricture Development - Baghdadi, Osama; Clark, Susannah; Ngo, Peter; Yasuda, Jessica; Staffa, Steven; Zendejas, Benjamin; Hamilton, Thomas; Jennings, Russell; Manfredi, Michael (Frontiers in Pediatrics, 2021)
Background and Aims: Children with esophageal atresia (EA) who undergo surgical repair are at risk for anastomotic stricture, which may need multiple dilations or surgical resection if the stricture proves refractory to endoscopic therapy. To date, no studies have assessed the predictive value of anastomotic diameter on long-term treatment outcomes. Our aim was to evaluate the relationship between anastomotic diameter in the early postoperative period and need for frequent dilations and stricture resection within 1 year of surgical repair. Methods: A retrospective chart review was performed of patients who had EA repair or stricture resection (SR). Medical records were reviewed to evaluate the diameter of the anastomosis at the first endoscopy after surgery, number and timing of dilations needed to treat the anastomotic stricture, and need for stricture resection. A generalized estimating equations (GEE) modeling with a logit link and binomial family was done to analyze the relationship between initial endoscopic anastomosis diameter and the outcome of needing a stricture resection. Median regression was implemented to estimate the association between number of dilations needed based on initial diameter. Results: A total of 121 patients (56 females) with a history of EA (64% long-gap EA) were identified who either underwent Foker repair at 46% or stricture resection with end-to-end esophageal anastomosis at 54%. The first endoscopy occurred a median of 22 days after surgery. Among all cases, a narrower anastomoses were more likely to need stricture resection with an OR of 12.9 (95% CI, 3.52, 47; p < 0.001) in patients with an initial diameter of <3 mm. The number of dilations that patients underwent also decreased as anastomotic diameter increased. This observation showed a significant difference when comparing all diameter categories when looking at all surgeries taken as a whole (p < 0.008). Conclusion: Initial anastomotic diameter as assessed via endoscopy performed after high-risk EA repair predicts which patients will require more esophageal dilations as well as the likelihood for stricture resection. This data may serve to stratify patients into different endoscopic treatment plans.